'Enough is Enough': songs and messages about alcohol in remote Central Australia. Issue 2 (14th April 2016) - Carfoot, Gavin
Abstract: This article examines some of the ways in which Australia's First Peoples have responded to serious community health concerns about alcohol through the medium of popular music. The writing, performing and recording of popular songs about alcohol provide an important example of community-led responses to health issues, and the effectiveness of music in communicating stories and messages about alcohol has been recognised through various government-funded recording projects. This article describes some of these issues in remote Australian Aboriginal communities, exploring a number of complexities that arise through arts-based 'instrumentalist' approaches to social and health issues. It draws on the author's own experience and collaborative work with Aboriginal musicians in Tennant Creek, a remote town in Australia's Northern Territory.